PERANAN PENGHULU TERHADAP HAK ULAYAT DI MINANGKABAU - Eviandi Ibrahim (JCH (Jurnal Cendekia Hukum), 2020)
Sumatra in general and Banuhampu District in particular the existence of customary rights is decreasing day by day both in terms of quantity and quality. The reduced existence of customary rights is because the customary rights have been traded by the legal community, in the case that Minangkabau customary law prohibits the sale and purchase of customary rights, this is stated in the customary kato "Jua indak eaten by bali, pawning indak eaten sando" means that ulayat rights can not be traded and transferred ownership to parties outside the legal community fellowship. Based on the above, the authors are interested in conducting research with the following problems: How are customary rights in Banuhampu District? What is the role of the leader / Pangatuo of the tribe / clan or the head of the inheritance of the ulayat rights in Banuhampu? What is the solution taken to defend the existence of customary rights in Banuhampu District? This research is juridical-social, because the researcher will examine how the application of law, namely customary law, in the development of the existence of customary rights among the Banuhampu community. Based on the discussion that the author puts forward, the following conclusions can be drawn: Whereas Customary Land (Ulayat) Currently its existence in Banuhampum can still be maintained. Even though it's been much less. This can be proven that until now the Legal Alliance in the Customary Law Community, namely Nagari, Tribe, Kaum, are still alive and existent, and each Legal Alliance still has customary rights although both in terms of quantity and quality have decreased. Whereas Ninik mamak / Penghulu / Pangatuo Suku / Kaum is a person who plays a very big role in the midst of his community / association, because ninik mamak has the right and obligation to take care of his children and nephews along with their communal customary rights, and has the obligation to preserve their customary rights. Whereas the customary rights must be maintained, because the ulayat rights are the identity of the association and the ulayat rights are not property rights, therefore the ulayat rights are prohibited from being transferred or sold.